PENGEMBANGAN SISTEM MANAJEMEN KEPENDUDUKAN DAN INFORMASI DAERAH BERBASIS WEB PEDUKUHAN BANJENG - Umar Jihad; Deddy Rahmadi (LPPI UMN AL WASHLIYAH, 2026)
This community service activity aims to develop a web-based Population Management and Regional Information System in Pedukuhan Banjeng. The primary issue identified was that population data management was still conducted manually, making it prone to recording errors, data duplication, and delays in information delivery. Through this community service initiative, a web-based system was designed and implemented to support population data recording, regional information management, and report generation in a more effective and efficient manner. The methods employed included observation, interviews with local administrative staff, system design, implementation, and user training for the partners. The results indicate that the developed system improves data management efficiency and facilitates easier access to information for the local administrators. With the implementation of this system, administrative processes have become more organized, transparent, and well-documented.